RADIUM-223. PLACE IN THE TREATMENT OF METASTATIC CASTRATION-REFRACTORY PROSTATE CANCER - A. A. Kostin; A. G. Muradyan; A. O. Tolkachev; S. V. Popov (Исследования и практика в медицине)
Patients with castration-refractory prostate cancer (PC) are a complicated group of patients for treatment. At the time of diagnosis, 85% of patients have a localized tumor process, however, in 40% of patients, generalization of the tumor process is observed. The most common localization of prostate cancer metastasis is the skeletal bone, which affects up to 90% of cases.At the same time, taking into account the increase in the morbidity of prostate cancer pathology, it dictates the need to search for new, more effective methods of treatment for this group of patients. Currently, there are six effective methods of treatment of metastatic castration-refractory prostate cancer (mCRPC): effects on androgenic stimulation (abiraterone acetate, enzalutamide); chemotherapy with drugs from the taxane group (docetaxel, cabazitaxel); immunotherapy (Sipuleucel-T), radionuclide therapy with Radium-223 chloride (Ksofigo®). 223Ra is a tropic to bone tissue alpha emitter, which, due to its high linear energy transfer and short transmission distance, provides an enhanced localized antitumor effect due to higher energy delivery. The article presents a literature review highlighting the mechanisms of development of castration refractoriness, the characteristic and efficacy of Radium-223 in the treatment of patients with metastatic castration-refractory prostate cancer.